2020
DOI: 10.1111/cts.12787
|View full text |Cite
|
Sign up to set email alerts
|

Associations of CYP2C9 and CYP2C19 Pharmacogenetic Variation with Phenytoin‐Induced Cutaneous Adverse Drug Reactions

Abstract: The role of cytochrome P450 (CYP)2C9 and CYP2C19 genetic variation in risk for phenytoin‐induced cutaneous adverse drug events is not well understood independently of the human leukocyte antigen B (HLA‐B)*15:02 risk allele. In the multi‐ethnic resource for Genetic Epidemiology Research on Adult Health and Aging (GERA) cohort, we identified 382 participants who filled a phenytoin prescription between 2005 and 2017. These participants included 21 people (5%) who self‐identified as Asian, 18 (5%) as black, 29 (8%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The CYP2C9 nonsynonymous variants with abnormal catalytic activity have been associated with altered metabolism of many drug substrates including warfarin 99 . Patients with low enzyme activity are at risk of CYP2C9 substrate‐related ADRs 100–102 …”
Section: Genetic Determinants Of Response Variability To Ketamine And...mentioning
confidence: 99%
See 1 more Smart Citation
“…The CYP2C9 nonsynonymous variants with abnormal catalytic activity have been associated with altered metabolism of many drug substrates including warfarin 99 . Patients with low enzyme activity are at risk of CYP2C9 substrate‐related ADRs 100–102 …”
Section: Genetic Determinants Of Response Variability To Ketamine And...mentioning
confidence: 99%
“…99 Patients with low enzyme activity are at risk of CYP2C9 substrate-related ADRs. [100][101][102] Although CYP2C9 plays a minor role in the metabolism of ketamine, in vitro studies showed differential catalytic activity of CYP2C9 variants on ketamine metabolism. 97 Zheng et al evaluated the catalytic activity of 38 CYP2C9 alleles on ketamine metabolism in vitro.…”
Section: Cyp2c9mentioning
confidence: 99%
“…The proxy polymorphisms rs10484555 and rs1061235 were used to confirm the presence of HLA-B*15:02 and HLA-A*31:01 respectively [24,25] and were examined in the Integrative Genomics Viewer (IGV) tool [26]. We selected further genes and single nucleotide polymorphisms reported to be associated with drug and/or metabolite level or maintenance dosing of aromatic ASMs [27][28][29][30]…”
Section: Hla-a*31:01 and Hla-b*15:02 Variant Genotypingmentioning
confidence: 99%
“…The carriers of allelic variants of CYP2B6 T983C were in 4.2-fold higher risk to develop SJS/TEN due to low clearance of nevirapine ( Ciccacci et al, 2013 ). Studies showed the variation in drug clearance enzyme CYP2C9*3 contributed to phenytoin-related SCARs with reduced drug clearance rate ( Chung et al, 2014 ; Tassaneeyakul et al, 2016 ; Wu et al, 2018 ; Su et al, 2019 ; Sukasem et al, 2020b ; Fohner et al, 2020 ), independently of HLA-B*15:02 risk allele. Glutathione-S-transferases (GST), which is a family of metabolic enzyme, plays a crucial role in the drug detoxification and activates some chemicals in a few cases.…”
Section: Genetic Variants and Sjs/tenmentioning
confidence: 99%